Overview of Virus Metagenomic Classification Methods and Their Biological Applications - Nooij, Sam; Schmitz, Dennis; Vennema, Harry; Kroneman, Annelies; Koopmans, Marion P. G. (Frontiers in Microbiology, 2018)
Metagenomics poses opportunities for clinical and public health virology applications by offering a way to assess complete taxonomic composition of a clinical sample in an unbiased way. However, the techniques required are complicated and analysis standards have yet to develop. This, together with the wealth of different tools and workflows that have been proposed, poses a barrier for new users. We evaluated 49 published computational classification workflows for virus metagenomics in a literature review. To this end, we described the methods of existing workflows by breaking them up into five general steps and assessed their ease-of-use and validation experiments. Performance scores of previous benchmarks were summarised and correlations between methods and performance were investigated. We indicate the potential suitability of the different workflows for 1) time-constrained diagnostics, 2) surveillance and outbreak source tracing, 3) detection of remote homologies (discovery), and 4) biodiversity studies. We provide two decision trees for virologists to help select a workflow for medical or biodiversity studies, as well as directions for future developments in clinical viral metagenomics.